Enhancing adoption of food safety measures in urban vegetable production and marketing systems - Keraita, Bernard N.; Amoah, Philip; Drechsel, Pay; Akple, Maxwell Selase Kwasi (2014)
Urban vegetable production and marketing systems in low-income countries are prone to contamination from polluted irrigation water, use of manure as fertilizer, unsanitary market conditions and other improper postharvest handling practices. In the recent past, the multiple-barrier approach has been adapted in research to develop measures to reduce contamination at different levels on the food chain. However, adoption of these measures could be constrained by low awareness levels of risks and risk-reduction measures as well as lack of adoption incentives. This paper presents various approaches and practical considerations that could enhance adoption rates of these measures, based on lessons learned from extensive studies carried out in Ghana. These studies include participatory development of risk reduction measures where end-users are actively involved in the process, incorporating their perceptions, needs and constraints. In addition, relevant social marketing techniques, incentive systems, awareness creation/education strategies and appropriate regulation measures are described. However, for optimal adoption, a combined framework of the most relevant approaches is advised.